PENGARUH SANKSI DENDA DAN PENDAPATAN WAJIB PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK PADA PELAKU UMKM - Rahmat Yuliansyah; Desy Amaliati Setiawan; Bayu Pratama; Meliana Sistin (Bajang Institute, 2025)
The purpose of this study is to investigate whether tax penalties and income levels have an impact on the tax compliance of MSME actors. The study was conducted using a quantitative research method, and data was collected by distributing questionnaires through Google Forms and WhatsApp social media to MSMEs in Jakarta. The findings of the study indicate that: (1) Fines have an influence on the compliance of MSME actors regarding tax payments. The likelihood of taxpayers fulfilling their obligations increases when tax sanctions are implemented. (2) The income level of MSME actors affects their compliance with tax payments. MSMEs with higher income or turnover are more likely to comply with their tax obligations. There is a significant and positive correlation between fines, income levels, and tax compliance for MSMEs in Jakarta.